2021
DOI: 10.1126/sciadv.abh3032
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SARS-CoV-2–induced pathways reveals drug repurposing strategies

Abstract: The global outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) necessitates the rapid development of new therapies against coronavirus disease 2019 (COVID-19) infection. Here, we present the identification of 200 approved drugs, appropriate for repurposing against COVID-19. We constructed a SARS-CoV-2–induced protein network, based on disease signatures defined by COVID-19 multiomics datasets, and cross-examined these pathways against approved drugs. This analysis identified 200 drugs pred… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 71 publications
1
34
0
Order By: Relevance
“…Knowing those facts would increase the chances of identifying potential prognostic markers and targets that would provide more efficient pandemic extinguishing. So far, we are focused on two approaches, i.e., looking for analogy in other pandemics and using the drugs/strategies that already exist or identifying novel ones [42]. However, apart from a pretty obvious solution, i.e., vaccination (will be addressed further), there are still some alternative approaches that we consider.…”
Section: Potential Therapeutic Strategies Towards Covid-19mentioning
confidence: 99%
“…Knowing those facts would increase the chances of identifying potential prognostic markers and targets that would provide more efficient pandemic extinguishing. So far, we are focused on two approaches, i.e., looking for analogy in other pandemics and using the drugs/strategies that already exist or identifying novel ones [42]. However, apart from a pretty obvious solution, i.e., vaccination (will be addressed further), there are still some alternative approaches that we consider.…”
Section: Potential Therapeutic Strategies Towards Covid-19mentioning
confidence: 99%
“…With proteomics data of IAVs [95,96], proteomic analyses can be performed to identify novel drug targets and drug repurposing strategies as previously applied to SARS-CoV-2 [97]. Taking a host-directed therapy approach [98], the constructed SARS-CoV-2induced protein artificial neural network cross-examined disease signatures and approved drugs, identifying 200 drugs with 40 already in clinical trials and 2 (proguanil and sulfasalazine) demonstrated to inhibit replication [97]. Applying such an approach to the H5N8 subtype and extended IAVs, understanding these metabolic perturbations are key in identifying novel and repurposing existing drugs to target them [99].…”
Section: Design-build-test-learn Cycle For H5n8mentioning
confidence: 99%
“…Previously, we have applied a drug repurposing strategy to identify potential new treatments for COVID-19 [7] . In this study, we use a similar computational approach, but include datasets from cells infected with either SARS-CoV-2 or SARS-CoV.…”
Section: Introductionmentioning
confidence: 99%